PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DALAM PENANAMAN NILAI-NILAI KEARIFAN LOKAL DI SMP MUHAMMADIYAH 9 WATUKEBO - Noval Aldika Putra; Siti Nursyamsiyah; Dhian Wahana Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Islamic Religious Education (PAI) plays an important role in shaping students' character and promoting the internalization of local wisdom values. This study aimed to determine the influence of Islamic Religious Education materials on the internalization of local wisdom values among eighth-grade students at SMP Muhammadiyah 9 Watukebo. This study used an associative quantitative approach with a population of 116 students, all of whom were used as the sample through a total sampling technique. The research instrument was a Likert-scale questionnaire consisting of 20 items measuring the Islamic Religious Education variable and 10 items measuring the Local Wisdom variable. The validity test indicated that all items were valid, while the reliability test yielded Cronbach's Alpha coefficients of 0.768 and 0.656 respectively. The normality test showed that the data were normally distributed (Sig. = 0.059) and the linearity test showed a linear relationship between the two variables (Sig. = 0.000). Simple linear regression analysis produced an R Square value of 0.194, indicating that Islamic Religious Education materials contributed 19.4% to the internalization of local wisdom values, while the remaining 80.6% was influenced by other factors outside this study, such as school culture, teacher role modeling, and the family and community environment. It can therefore be concluded that Islamic Religious Education materials have a significant, although weak, influence on the internalization of local wisdom values among students at SMP Muhammadiyah 9 Watukebo.